Nursing ethical decision making on adult physical restraint: a scoping review - Cortinhal, Vanessa Sofia Jorge (2024)
OBJECTIVE: to map the existing knowledge on nursing ethical decision making in the physical restraint of hospitalised adults. (1) Background: physical restraint is a technique that conditions the free movement of the body, with risks and benefits. The prevalence of physical restraint in healthcare suffers a wide variation, considering the environment or pathology, and it raises ethical issues that hinders decision making. This article intends to analyse and discuss this problem, starting from a literature review that will provoke a grounded discussion on the ethical and legal aspects. Inclusion criteria are: studies on physical restraint (C) and ethical nursing decision making (C) in hospitalized adults (P); (2) methods: a three-step search strategy was used according to the JBI. The databases consulted were CINAHL Plus with Full Text (EBSCOhost), MEDLINE Full Text (EBSCOhost), Nursing and Allied Health Collection: Comprehensive and Cochrane Database of Systematic Reviews (by Cochrane Library, RCAAP and Google Scholar. All articles were analysed by two independent reviewers; (3) results: according to the inclusion criteria, 18 articles were included. The categories that influence ethical decision in nursing are: consequence of the decision, the context, the nature of the decision in terms of its complexity, the principles of the ethical decision in nursing, ethical issues and universal values; (4) conclusions: the findings of this review provide evidence that there is extensive knowledge regarding nursing ethical decision making in adult physical restriction, also, it is considered an ethical issue with many associated assumptions. In this article we aim to confront all these issues from a legal perspective.